Morphometric, meristic and genetic differeniation of juvenile yellowfin tuna Thunnus albacares (Bonnaterre,1788) and Bigeye tuna Thunnus obesus (Lowe,1839) - Pedrosa, Ivane R. (Miagao, Iloilo University of the Philippines, 2012)
Doubts on the realibity of yellow fin tuna, Thunnus albacares, and bigeye tuna, T. obesus, catch data arise since cases of misidentification are common for both species, especially at sizes less than 40 cm. Suitable methods for identification of juveniles of these tuna species were determined through morphological, meristic, and genetic investigations. Principal Component and Cluster Analyses were not able to separate individuals using morphometric and meristic data while mtDNA D-loop control region sequence information using Neighbor-Joining method for phylogenetic analysis clearly separated juveniles of both species. Liver morphology was also investigated, and species discrimination based on right lobe length criterion, matched with genetics data. These results suggest that apart from DNA-based markers, liver morphology can be used as basis for discrimating juveniles of these two species. Moreover,, liver morphology assessment could be considered as a practical means for species identification that can be adopted by enumerators in the field.
Thesis (M.S. Fisheries-Fisheries Biology) -- Miagao, Iloilo : University of the Philippines in the Visayas, April 2011.
Thesis (M.S. Fisheries-Fisheries Biology) -- Miagao, Iloilo : U.P. Visayas, April 2011.
Keywords: Thunnus albacares; Yellowfin tuna; Thunnus obesus; Bigeye tuna